(untitled) (CIPEEX, 2022)
THIS IS AN INTEGRATIVE LITERATURE REVIEW THAT AIMS TO DESCRIBE THE EFFECTS OF COMPLEMENTARY THERAPIES ON WOMEN’S QUALITY OF LIFE DURING PREGNANCY AND VAGINAL LABOR. COMPLEMENTARY AND INTEGRATIVE THERAPIES ARE PRACTICES THAT ASSIST IN THE TREATMENT OF DISEASES AND ADVERSE HEALTH CONDITIONS. PREGNANCY AND CHILDBIRTH ARE PERIODS OF MANY CHANGES AND HEALTH PROFESSIONALS MUST HELP WOMEN GO THROUGH THIS PERIOD. COMPLEMENTARY THERAPEUTIC METHODS ARE A SAFE AND PROVEN WAY TO RELIEVE THE UNPLEASANT SYMPTOMS OF PREGNANCY AND CHILDBIRTH, REDUCING THE USE OF UNNECESSARY MEDICATION THAT CAN BRING RISKS TO THE MOTHER’S AND BABY’S HEALTH. THESE TECHNIQUES ARE RECOGNIZED BY THE WORLD HEALTH ORGANIZATION (WHO). THIS STUDY HAD A FINAL SAMPLE CONSISTING OF 18 ORIGINAL ARTICLES, SEARCHED IN THE DATABASES OF THE VIRTUAL HEALTH LIBRARY (VHL), PUBMED, SCIENTIFIC ELECTRONIC LIBRARY OLINE (SCIELO), AND THE GOOGLE ACADEMIC SEARCH ENGINE. THE SELECTED THERAPIES WERE DULY GROUPED INTO FOUR CATEGORIES: BODY-MIND MEDICINE, BIOLOGICALLY BASED TREATMENTS, BODY MANIPULATION METHODS, AND ENERGY MEDICINE. ACCORDING TO THIS CATEGORIZATION, THE EFFECTS OF EACH THERAPY WERE LISTED, AND THEY SHOWED SEVERAL BENEFITS, SUCH AS THE RELIEF OF STRESS, ANXIETY, AND PAIN, NORMALIZATION OF BLOOD SUGAR AND BLOOD PRESSURE, AMONG OTHERS. THE EXERCISE OF THE VARIOUS INTEGRATIVE AND COMPLEMENTARY PRACTICES BRINGS NUMEROUS BENEFITS FOR MATERNAL-FETAL HEALTH BOTH IN THE GESTATIONAL PERIOD AND IN CHILDBIRTH.